Metacognitive Failures of Preservice Mathematics Teachers ın Problem Solving - Betül Kaya, Zeyneb; Kepceoglu, Ibrahim (Athens Institute for Education and Research ATINER, 2022)
Metacognitive success is one of the factors that positively affects problem solving skills. Identifying metacognitive failures in the problem-solving process is also important in recognizing the factors that will inhibit metacognitive success. In this study, it is aimed to reveal metacognitive failures of pre-service mathematics teachers in the process of given mathematical problems. The present research on investigated metacognitive failures of pre-service teachers in the process of problem solving is modelled as case study. Data collection was carried out in clinical interviews were conducted with the preservice teachers who were predicted to obtain rich data in accordance with the purpose, using the “think aloud” interview technique, among these pre-service teachers. As a result of the analysis of the data and field notes obtained from the clinical interview voice recordings, 8 different metacognitive failure behaviors were encountered; including “metacognitive mirage” two times, “metacognitive blindness” three times and “metacognitive vandalism” three times. Keywords: metacognitive failure, preservice teacher, mathematics education
Keywords: 4. Education